Medication‐related 30‐day rehospitalizations in palliative care patients. Issue 6 (26th July 2020) - Pruskowski, Jennifer A.; Ruby, Christine M.; Berenbrok, Lucas A.; Seybert, Amy L.; Handler, Steven M.
Abstract: Purpose: Prior studies suggest that inpatient palliative care services can reduce rehospitalizations. However, medications commonly prescribed by palliative care providers (eg, opioids, benzodiazepines, and antipsychotics) have been independently associated with rehospitalizations. Little is known regarding the role of adverse drug reaction (ADR)‐related rehospitalizations within the palliative care population. Objective: To determine the prevalence and explore predictors of ADR‐related 30‐day rehospitalizations in an inpatient palliative care population. Methods: A retrospective cohort study that included 284 palliative care patients who were readmitted within 30‐days of discharge from two academic hospitals in Western Pennsylvania. All unplanned rehospitalizations were assessed for medication causality via the Naranjo algorithm by at least two independent reviewers. Results: The mean (SD) age of the cohort was 61 (16) years and included 45% (n = 127) female and 81% Caucasians (n = 229). Of the 254 unplanned rehospitalizations, 11 (4%) were classified as doubtful ADRs, 224 (88%) were classified as possible ADRs, and 19 (7%) were defined as probable or definite ADR‐related. Tacrolimus was associated with three probable and one definite ADR‐related rehospitalization. Oncologic agents (eg, venetoclax, nivolumab, vincristine, and decitabine, carfilzomib; n = 5), anticoagulants (eg, rivaroxaban, apixaban, and warfarin; n = 4), antimicrobials (eg, cephalexin and vancomycin; n = 2), potassium chloride (n = 2), lorazepam (n = 1), and nicotine replacement (n = 1) were all associated with probable ADRs. Only the number of medication changes during the index admissions was observed as a statistically significant predictor of rehospitalizations in this population ( P = .043). Conclusions: Palliative care patients often suffer from potential ADR‐related rehospitalizations and the number of medication changes during the index hospital admissions is associated with future potential ADRs. Clinical pharmacists should consider these findings when developing initiatives to reduce rehospitalizations in the inpatient palliative care patient population.